Tradisi Rokatan Calon Pengantin Perspektif Fenomenologi - husen, muhammad nur; Laili, Afrohatul (Fakta: Forum Aktual Ahwal Al-Syakhsiyah, 2023)
Marriage is one of the ceremonial which makes the union of two souls, become a family through akad agreement set by religious rules. The series of marriage procession couldnot be separated with the custom. One of the traditions that stick around on the wedding procession in the society of SelogudigVillage is Rokatan. Rokatan procession is ruwatan procession or ritual, ruwatan tradition by bride-groom to be which would be holdin the wedding ceremonial. The majority of Selogudig’s society argues that there are many values and benefits contained in this Rokat bride-groom to be tradition, just like to get blessing and salvation, especially for family’s long life become a better family or either called sakinah mawaddah and wa rahmah. On the other hand, the core term of rokat is saving the life, from both of the nuisance that can be seen by the sense of sight or the nuisance of the creature (spirit). For the society who agree or accept this rokat traditions, assume that this ritual is nota ritual act of far-fetched, because behind this rokat traditions there is the meaning as an effort to save yourself from all distractions and to be closer to his God. However, for the groups who disagree or unaccepted this rokatbride-groom to be, reasoned that rokatan is one of ritual heresy as well as his actions closer to the polytheists.